Geographically weighted regression analysis of incomplete basic childhood vaccination in Sub-Saharan Africa: Evidence from DHS, 2019–2024 - Tigist Kifle Tsegaw; Eyob Akalewold Alemu; Fetlework Gubena Arage; Zinabu Bekele Tadese; Eliyas Addisu Taye; Tsegasilassie Gebremariam Abate (PLoS ONE, 2025)
Background Immunization is the safest way to protect against disease. Currently, vaccination saves more than 4 million lives annually. By 2030, 90% of people worldwide are expected to have received the basic immunizations, according to the Immunization Agenda 2030 (IA2030). However, in sub-Saharan Africa (SSA), only 54.1% of children receive the complete set of basic childhood vaccinations. Therefore, this study aims to assess the spatial variation of incomplete basic childhood vaccination and its determinants in SSA by using DHS data from 2019–2024. Method For our study, we utilized a total of 28,045 weighted children from 16 selected SSA countries. The vaccination status was determined through both maternal recall and the use of vaccination cards. Spatial autocorrelations, hotspot analysis, spatial interpolation, and SaTScan analysis were conducted to explore the spatial distribution. Ordinary Least Squares (OLS) and Geographical Weighted Regression (GWR) were performed to identify the associated factors of partial immunization. Results The pooled prevalence of partial immunization in SSA was 35.5% [95% CI: 28.49%, 42.51%]. Mauritania, Gabon, Côte d’Ivoire, central Tanzania, Liberia, and northeast Mozambique are among the hotspot regions that have been identified. Higher maternal education, female-headed households, maternal age between 15 and 24 years, absence of antenatal care, and urban residency were all found to be significant predictors with GWR analysis. Conclusion In SSA, partial immunization shows a clustered spatial pattern with different hotspot areas. The use of maternal health services and socio-demographic factors has an impact on incomplete immunization. Improving vaccination coverage requires focused programs that address awareness creation and service utilization.